Genotype-Specific Concordance of Chlamydia trachomatis Genital Infection Within Heterosexual Partnerships. Issue 12 (December 2016) - Schillinger, Julia A.; Katz, Barry P.; Markowitz, Lauri E.; Braslins, Phillip G.; Shrier, Lydia A.; Madico, Guillermo; Van Der Pol, Barbara; Orr, Donald P.; Rice, Peter A.; Batteiger, Byron E.
Abstract : Background: Sexual transmission rates of Chlamydia trachomatis ( Ct ) cannot be measured directly; however, the study of concordance of Ct infection in sexual partnerships (dyads) can help to illuminate factors influencing Ct transmission. Methods: Heterosexual men and women with Ct infection and their sex partners were enrolled and partner-specific coital and behavioral data collected for the prior 30 days. Microbiological data included Ct culture, and nucleic acid amplification testing (NAAT), quantitative Ct polymerase chain reaction, and ompA genotyping. We measured Ct concordance in dyads and factors (correlates) associated with concordance. Results: One hundred twenty-one women and 125 men formed 128 dyads. Overall, 72.9% of male partners of NAAT-positive women and 68.6% of female partners of NAAT-positive men were Ct -infected. Concordance was more common in dyads with culture-positive members (78.6% of male partners, 77% of female partners). Partners of women and men who were NAAT-positive only had lower concordance (33.3%, 46.4%, respectively). Women in concordant dyads had significantly higher median endocervical quantitative Ct polymerase chain reaction values (3, 032) compared with CT-infected women in discordant dyads (1013 inclusion forming units DNA equivalents per mL; P < 0.01). Among 54 Ct -concordant dyads with ompA genotype data for both members, 96.2% had identical genotypes. Conclusions: Higher organism load appears associated with concordance among women. Same-genotype chlamydial concordance was high in sexual partnerships. No behavioral factors were sufficiently discriminating to guide partner services activities. Findings may help model coitus-specific transmission probabilities. Abstract : We found high rates of same-genotype Chlamydia trachomatis infection in heterosexual partnerships; among women, higher chlamydial organism load was associated with chlamydial infection among their male partners.